La resección diafisiaria en la osteomielitis - Valls, José (1937)
The authors present five cases of diaphysic resection in osteomyelitis. One case of osteomyelitis with primary precocious resection, one case of acute osteomyelitis with secondary resection, and three cases of osteomyelitis : one with compound fracture, and two cases of very acute flare up, of chronic focus of infectious treated by late resections. In all cases the diaphysic resection was followed by a good regeneration of bone. In one of the cases, continuous irrigation with Carrel-Dakin solution was done post-operatively, and in the other four Orr's method was utilized. The authors state that they have the impression that the diaphysic resection will occupy each time a greater place amongst the therapeutic mesures to be applied against osteomyelitis.